Sistem Informasi Eksekutif Pelelangan dengan Metode Iconix Process Pada PT. Pelindo I Berbasis Web - Dedek Indra Gunawan Hutasuhut; Ambiyar Ambiyar; Nita Syahputri; Ulfa Indriani; Ermayanti Astuti; Unung Verawardina (STMIK Budi Darma, 2021)
The advancement of information technology has had a tremendous impact in assisting executives in making decisions. The executive information system is one of the best methods to help the leader or executive to make decisions effectively and efficiently. Not all work and procurement of goods is carried out by employees or staff of PT. Pelindo I, however, was carried out through an auction process. So far, the data collection process has been done using Microsoft Excel. Many weaknesses that occur, namely the data is not realtime and the leader cannot see the information directly and the data displayed cannot help the leader make decisions quickly. Therefore, an Executive Information System is needed so that the leadership can see directly the status of the existing auction at PT. Pelindo I. The purpose of this research is to design and build an executive information system at PT. Pelindo I with the iconix process method to display the status of the auction. The stages in designing an application using the Iconix Process method consist of nine stages, namely the process of requirements analysis, preparation of a domain model, GUI storyboard, use case diagrams, robustness diagrams, sequence diagrams, domain updates model, class diagram, implementation. The result of this research is to produce an application that displays a report on the status of the existing auction at PT. Pelindo in 2019 which is more efficient by using the iconix process method. The report that is displayed is in the form of data on contract completion, still in process, failed and returned.